Ab initio study of the optoelectronic properties of α-Ba2SnS4. (1st November 2022) - Ben Smida, Youssef; Ferjani, Hela; Boukhachem, Abdelwaheb; Onwudiwe, Damian C.; Elamin, Nuha Y.; Hamzaoui, Ahmed Hichem
Abstract: The electronic structure and optical properties of a ternary thiostannate compound (α-Ba2 SnS4 ) have been successfully predicted via ab initio calculations. Optimized structure was confirmed by both Bond Valence Sum (BVS) and charge distribution (CHARDI) validation models, which showed a reduction in the coordination number of the barium atom after structure optimization. The band structure confirmed that the α-Ba2 SnS4 is a semiconductor material with a direct band gap, and the calculated band gap energy was 2.469 eV which was in good agreement with other literature reports. Calculated optical spectra (dielectric function, refractive index, reflectivity, absorption, energy loss function) of the compound exhibited a significant optical anisotropy. A plot of the dielectric function showed four transition frequencies, while the determinate frequencies values were consistent with the density of states. A high absorptivity of the electromagnetic waves in both visible and near UV regions was observed in the absorption spectra, which indicated the possible application of this compound in optoelectronic field as photocatalysts. The mechanical stability of this compound has been verified by the phonon calculation.